Immunohistochemistry in postmortem diagnosis of acute cerebral hypoxia and ischemia: A systematic review. Issue 25 (25th June 2021) - Barranco, Rosario; Bonsignore, Alessandro; Ventura, Francesco
Abstract: Background: : Discovery of evidence of acute brain ischemia or hypoxia and its differentiation from agonal hypoxia represents a task of interest but extremely difficult in forensic neuropathology. Generally, more than 50% of forensic autopsies indicate evidence of brain induced functional arrest of the organ system, which can be the result of a hypoxic/ischemic brain event. Even if the brain is the target organ of hypoxic/ischemic damage, at present, there are no specific neuropathological (macroscopic and histological) findings of hypoxic damage (such as in drowning, hanging, intoxication with carbon monoxide) or acute ischemia. In fact, the first histological signs appear after at least 4 to 6 hours. Numerous authors have pointed out how an immunohistochemical analysis could help diagnose acute cerebral hypoxia/ischemia. Data sources: This review was based on articles published in PubMed and Scopus databases in the past 25 years, with the following keywords "immunohistochemical markers, " "acute cerebral ischemia, " "ischemic or hypoxic brain damage, " and "acute cerebral hypoxia". Objectives: : Original articles and reviews on this topic were selected. The purpose of this review is to analyze and summarize the markers studied so far and to consider the limits of immunohistochemistry that exist to date in this specific field of forensic pathology. Results: : We identified 13 markers that had been examined (in previous studies) for this purpose. In our opinion, it is difficult to identify reliable and confirmed biomarkers from multiple studies in order to support a postmortem diagnosis of acute cerebral hypoxia/ischemia. Microtubule-associated protein 2 (MAP2) is the most researched marker in the literature and the results obtained have proven to be quite useful. Conclusion: Immunohistochemistry has provided interesting and promising results, but further studies are needed in order to confirm and apply them in standard forensic practice.